2017
DOI: 10.15406/mojor.2017.08.00298
|View full text |Cite
|
Sign up to set email alerts
|

Clavicle Fracture Open Reduction Internal Fixation: Results of Modern Technique

Abstract: Background: Clavicle fractures are common. Surgical treatment of displaced clavicle fractures is controversial. We present our experience with 68 patients over an 11 year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The mean time for clinical union of fracture was 8.77 weeks and the mean time for radiological union was 17.03 weeks (12-22 weeks) which was similar to the study done by Simonian TL et al was 19.28 weeks, E Mohamed et al was 14.2 weeks, Dhoju et al was 16 weeks and Olivier et al was 12 weeks. [27][28][29][30] In the study done by Poigenfuerst et al 9 patients out of 122 (7.3%) had superficial wound infection but no cases of osteomyelitis or infected pseudo arthritis. 13 Similarly E Mohamed et al found superficial skin infection in 1 of 15 patients (6.66%).…”
Section: Discussionmentioning
confidence: 99%
“…The mean time for clinical union of fracture was 8.77 weeks and the mean time for radiological union was 17.03 weeks (12-22 weeks) which was similar to the study done by Simonian TL et al was 19.28 weeks, E Mohamed et al was 14.2 weeks, Dhoju et al was 16 weeks and Olivier et al was 12 weeks. [27][28][29][30] In the study done by Poigenfuerst et al 9 patients out of 122 (7.3%) had superficial wound infection but no cases of osteomyelitis or infected pseudo arthritis. 13 Similarly E Mohamed et al found superficial skin infection in 1 of 15 patients (6.66%).…”
Section: Discussionmentioning
confidence: 99%